DETERMINANTS OF FINANCIAL DISTRESS IN INDONESIAN TEXTILE AND GARMENT COMPANIES EVIDENCE FROM 2017– 2019 - Legowo Dwi Resihono; Retnoningrum; Luluk Takari; Sri Hutami (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2026)
This study investigates the determinants of financial distress in Indonesian textile and garment firms listed on the Indonesia Stock Exchange during the 2017–2019 period. Specifically, it examines the effects of profitability (Return on Assets), liquidity (Current Ratio), leverage (Debt-to-Total-Assets Ratio), and activity (Fixed Asset Turnover) on the likelihood of financial distress. Using a quantitative approach, this study analyzes secondary data from 18 firms, resulting in 54 firm-year observations. Financial distress is proxied using the Altman Z-score and transformed into a binary variable. Logistic regression is employed to test both individual and joint effects of the explanatory variables. The findings reveal that liquidity and activity ratios significantly influence financial distress, while profitability and leverage do not exhibit significant individual effects. However, all variables jointly explain financial distress. The model demonstrates acceptable goodness of fit, with a Hosmer–Lemeshow significance of 0.538, classification accuracy of 79.6%, and a Nagelkerke R² of 0.476. These results suggest that short-term solvency and asset utilization efficiency play a more critical role than profitability and leverage in explaining financial distress in Indonesian manufacturing firms. This study contributes to the financial distress literature by providing industry-specific evidence from an emerging-market context and highlighting the importance of operational efficiency and liquidity management in asset-intensive industries.